2003
DOI: 10.1095/biolreprod.102.010595
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Inputs from the Hypothalamus and Brain Stem to the Medial Preoptic Area of the Ram: Neurochemical Correlates and Comparison to the Ewe1

Abstract: The retrograde tracer, FluoroGold, was used to trace the neuronal inputs from the septum, hypothalamus, and brain stem to the region of the GnRH neurons in the rostral preoptic area of the ram and to compare these imputs with those in the ewe. Sex differences were found in the number of retrogradely labeled cells in the dorsomedial and ventromedial nuclei. Retrogradely labeled cells were also observed in the lateral septum, preoptic area, organum vasculosum of the lamina terminalis, bed nucleus of the stria te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
3
14
0
1
Order By: Relevance
“…The location of FG-stained neurons (fig. 2A–C) is similar to that previously obtained in the sheep using the same technique [27, 39, 40]. In brief, large concentrations of FG cells were observed throughout the rostrocaudal extension of the arcuate nucleus (fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The location of FG-stained neurons (fig. 2A–C) is similar to that previously obtained in the sheep using the same technique [27, 39, 40]. In brief, large concentrations of FG cells were observed throughout the rostrocaudal extension of the arcuate nucleus (fig.…”
Section: Resultssupporting
confidence: 86%
“…Our distribution of FG retrogradely labeled neurons in the ovine hypothalamus is consistent with previous data in the ewe brain using FG [27, 39, 40]. However, little is known about the neuronal projections of steroid-receptive cells in the brain of non-rodent species.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, only 5% of the total TH-immunoreactive cell population was found to contain FG. This is similar to a study on the ram [25], where a mere 3% of TH neurons located in A12 and A14 contained FG when the tracer was injected into the rostral preoptic area. Indeed, Tillet et al [26] did not detect any FG/TH in the A12 dopaminergic nucleus.…”
Section: Discussionsupporting
confidence: 88%
“…However, high temperature antigen retrieval causes the complete bleaching of FG fluorescence from our sections and to perform quantitative analysis we had to take photographs before and after the antigen retrieval procedure. One advantage of this dual-photography approach is that it avoids FG fading following immunocytochemistry – a problem noted by others [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation